Relationship Between Sedentary Lifestyle, Physical Activity and Stress in University Students and Their Life Habits: A Scoping Review with PRISMA Checklist (PRISMA-ScR) - Mariasole Antonietta Guerriero; Anna Dipace; Antonietta Monda; Antonella De Maria; Rita Polito; Giovanni Messina; Marcellino Monda; Marilena di Padova; Angelo Basta; Maria Ruberto; Emanuele Capasso; Fiorenzo Moscatelli; et al. (Brain Sciences)
The global prevalence of sedentary lifestyles and the associated health risks, such as cardiovascular, metabolic and mental issues, is an epidemic worldwide problem, particularly in the university population. Background/Objectives: University students are particularly vulnerable because of academic pressure and lifestyle changes. Despite the well-known benefits of physical activity in reducing mental stress and improving physical and mental well-being, the literature lacks effective interventions and standardized protocols for this population. This study aims to investigate the state of the art in literature regarding the correlation between the use of physical activity as a means of prevention and intervention and the effects on university students’ stress and mental well-being. Methods: A scoping review was conducted using the PRISMA protocol for scoping reviews, targeting university population with specific terms. Results: The review analyzed 61 articles and identified a consistent positive correlation between physical activity and stress reduction. Interventions included yoga, tai chi, aerobic exercise and moderate- or high-intensity exercise. A lack of standardized protocols were also evident. Conclusions: Physical activity is an effective means for managing stress and improving mental well-being among university students. An integrated approach combining different forms of exercise and strategies to regulate emotions could provide very effective effects on the mental well-being of students. Universities should propose physical activity programs in several forms to enable students to choose the most appropriate one and keep them active.